Legitimasi Maslahat dalam Ijtihad Kalender: Studi Istiḥsān terhadap Kalender Hijriah Global Tunggal (KHGT) - Jundil Ikrom; Amir Tajrid; Mahsun Mahsun (Al-fiqh, 2026)
This article departs from the crucial problem of the absence of a unified Hijri calendar in the Muslim world, which has led to differences in the timing of worship, uncertainty in dating, and weak socio-religious integration among Muslims. This study aims to analyze Muhammadiyah’s Global Unified Hijri Calendar (Kalender Hijriah Global Tunggal/KHGT) from the perspective of al-maṣlaḥah and istiḥsān in usul al-fiqh, and to assess the extent to which KHGT can be justified as a valid form of ijtihad. This research employs a qualitative method with a library research approach. Data were obtained from classical usul al-fiqh works, academic books, scholarly journal articles, and official Muhammadiyah documents on KHGT. The data were processed using descriptive-analytical techniques and examined normatively by positioning al-maṣlaḥah and istiḥsān as evaluative instruments. The findings show that KHGT is not merely an astronomical formulation, but also a development of Muhammadiyah’s calendar ijtihad methodology from a local orientation toward a more planned, unified, and collectively beneficial global system. From the perspective of usul al-fiqh, KHGT may be understood as a valid form of istiḥsān, particularly through the approaches of istiḥsān bi al-al-maṣlaḥah and istiḥsān bi al-qiyās al-khafī, as long as it remains within the framework of naṣṣ, maqasid al-shari‘ah, and the discipline of usul al-fiqh. This article suggests that the development of a global Islamic calendar should continue to be accompanied by stronger usul al-fiqh argumentation and dialogue among religious authorities.